Antibiotic-Prescribed Infections in Patients Receiving Home Care Services - Aykanat Yurtsever, Burcu; Yurtsever, Ceyhun; Atasoy, Volkan; Hacısalihoğlu, Ayşenur (Tropical Health and Medical Research, 2023)
In our study, it was aimed to examine "antibiotic (AB) prescribed infections" (ABPI) in patients receiving home care service (HCS) in the last year. Patients receiving HCS from a tertiary hospital were evaluated (n=176). In addition to descriptive information such as demographics, devices used and chronic diseases, ABs prescribed to patients in the last year and infections that were the reason for their prescription were screened retrospectively. It was determined that 138 patients had been prescribed AB at least once. In total, 691 ABs were used in 550 prescriptions. It was observed that the most common ABPI was urinary tract infection (44.9%), and the most commonly prescribed AB was amoxicillin-clavulanic acid (n=123). Using assistive devices for breathing and lung disease increased the risk of lower respiratory tract infection, for which ABs were prescribed at least once. These predictive factors were feeding with a nasogastric catheter or percutaneous endoscopic gastrostomy for upper respiratory tract infections and using a urinary catheter for urinary tract infections. Our study revealed the most common ABPI in patients receiving HCS and the factors predicting them. These findings will shed light on the planning and management of HCS.